Determinasi Faktor Pendukung dan Hambatan dalam Pelaksanaan Strategi Mitigasi Bencana Banjir di Kecamatan Koto Tangah oleh Pemerintah Kota Padang - Ratonda, M. Rayhan; Alhadi, Zikri (PUBLICNESS: Journal of Public Administration Studies, 2024)
This This research aims to identify the supporting and inhibiting factors in the flood disaster mitigation strategy carried out by the Padang City government in Koto Tangah Sub-district. The study was conducted in several related agencies, including the Padang City Regional Disaster Management Agency (BPBD), the Padang City Environment Agency, and the Padang City PUPR Agency. Using a qualitative approach with descriptive methodology, data was collected through interviews, observation, and documentation, with primary and secondary data sources. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the supporting factors of flood disaster mitigation strategies in the Koto Tangah Sub-district include the commitment of the Padang City government, cooperation between agencies, technological support, and community participation and awareness. Meanwhile, the inhibiting factors include uncontrolled population growth and land use change, inadequate infrastructure, and lack of community awareness and participation.